Bioanalysis Zone: DBS survey results. (February 2014) - Denniff, Philip; Holliman, Chris; Svensson, Leif; Weng, Naidong; Patel, Shefali
Bioanalysis Zone carried out a survey to evaluate the use of and attitudes to DBS analysis among our readership in the bioanalytical community. DBS analysis has generated a huge amount of interest in recent years. We wanted to take a snapshot of the field and determine whether a consensus is emerging on the future of DBS. We asked you for your honest opinions and you delivered! You can view the full results at www.bioanalysis-zone.com. We have a selection of short opinion articles below, giving a range of viewpoints on the current and future use of DBS, alongside some of the survey results.